The Stepping Threshold Test for Reactive Balance: Validation of Two Observer-Based Evaluation Strategies to Assess Stepping Behavior in Fall-Prone Older Adults - Adams, Michael; Brüll, Leon; Lohkamp, Monika; Schwenk, Michael (Frontiers in Sports and Active Living, 2021)
Introduction Measurement of reactive balance, although critical for fall prevention, is severely underrepresented in the clinical setting as there is a lack of valid assessments. The Stepping Threshold Test (STT) is a newly developed, instrumented test for reactive balance on a movable platform, which, however, has not yet been validated for fall-prone older adults. Furthermore, different schemes of observer-based evaluation seem possible. The aim of this study was to investigate validity with respect to fall risk, interpretability and feasibility of the STT using two different evaluation strategies. Methods Seventy-one fall-prone older adults (65+) underwent progressively increasing perturbations in four directions (STT). Single and multiple step thresholds for each perturbation direction were determined via two observer-based evaluation schemes: 1) consideration of all steps (All-step-count evaluation, ACE) 2) consideration of those steps that extend the base of support in the direction of perturbation (Direction-sensitive evaluation, DSE). Established balance measures including global (Brief Balance Evaluations Systems Test, BriefBEST), proactive (Timed Up and Go, TUG) and static balance (8-level balance scale, 8LBS), as well as fear of falling (Short Falls Efficacy Scale – International, FES-I) and fall occurence in the past year served as reference measurements. Results The STT sum scores correlated moderately with the BriefBEST (ACE: r=0.413; DSE: r=0.388) and TUG (ACE: r=-0.379; DSE: r=-0.435) and low with the 8LBS (ACE: r=0.173; DSE: r=0.246) and Short FES-I (ACE: r=-0.108; DSE: r=-0.104). The sum scores did not distinguish between fallers and non-fallers. No floor/ceiling effects occurred for the STT sum score, but for specific STT thresholds for both ACE (mean floor effect=13.04%, SD=19.35%; mean ceiling effect=4.29%, SD=7.75%) and DSE (mean floor effect=7.86%, SD=15.23%; mean ceiling effect=21.07%, SD=26.08). No severe adverse events occurred. Discussion Correlations between the STT and other balance tests were in the expected magnitude, indicating convergent validity. The STT could not distinguish between fallers and non-fallers, referring a need for further studies and prospective surveys of falls to validate the STT. Current results do not allow a definitive judgment on the advantage of using ACE or DSE. Study results represent a step towards a reactive balance assessment application in a clinical setting.